2008
DOI: 10.1051/0004-6361:200810170
|View full text |Cite
|
Sign up to set email alerts
|

On the opacity change required to compensate for the revised solar composition

Abstract: Context. Recent revisions of the determination of the solar composition have resulted in solar models in marked disagreement with helioseismic inferences. Aims. The effect of the inferred composition change on the models is largely caused by the change in opacity. Thus, we wish to determine an intrinsic opacity change that would compensate for the revision to the composition. Methods. By comparing models computed with the old and revised compositions we determine the required opacity change. Models are compute… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
101
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 114 publications
(105 citation statements)
references
References 37 publications
4
101
0
Order By: Relevance
“…The inconsistent chemical abundance probably indicates that the opacity data need to be improved. In order to make the solar model with the new composition (Asplund et al 2005) agree with the helioseismic data, the opacity near the base of the convection zone needs to be increased by 10%-30% (Basu & Antia 2004;Christensen-Dalsgaard et al 2009). Much research has shown that the old compositions (Grevesse & Noels 1993;Grevesse & Sauval 1998) result in the correct R CZ (e.g., Christensen-Dalsgaard et al 1996;TurckChièze et al 1998;Brun et al 1999;Paxton et al 2011).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…The inconsistent chemical abundance probably indicates that the opacity data need to be improved. In order to make the solar model with the new composition (Asplund et al 2005) agree with the helioseismic data, the opacity near the base of the convection zone needs to be increased by 10%-30% (Basu & Antia 2004;Christensen-Dalsgaard et al 2009). Much research has shown that the old compositions (Grevesse & Noels 1993;Grevesse & Sauval 1998) result in the correct R CZ (e.g., Christensen-Dalsgaard et al 1996;TurckChièze et al 1998;Brun et al 1999;Paxton et al 2011).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…As a result of such a procedure, the initial metallicity Z and helium Y abundance are inferred. As largely debated in recent years (see e.g Bahcall et al 2005b;Basu & Antia 2008;Christensen-Dalsgaard et al 2009;Serenelli et al 2009, and references therein), the very good agreement between the SSM and the helioseismological constraints, mainly the sound speed profile, the extension of the convective envelope and the surface helium abundance, achieved at the end of the last century has been compromised by the new determinations of the metal abundances based on 3D photospheric models by Asplund et al (2005), and only slightly alleviated by the very recent release by Asplund et al (2009). With these caveats, the initial helium and metal abundance of the Sun provided by the current SSMs allow determination of the ΔY/ΔZ, once a primordial helium abundance Y P is chosen.…”
Section: Comparison With Independent Methodsmentioning
confidence: 99%
“…The effects of a decreasing metallicity can be mimicked by an increase in opacity. In fact, it has been shown that an increase in the radiative opacities in the range of 15 to 20% at the base of the convective zone, smoothly decreasing to 3 to 4% in the solar core, would suffice to reconcile AGSS09 composition with the helioseismic results (Bahcall et al, 2004;Christensen-Dalsgaard et al, 2009;Villante, 2010). This solution is very attractive, because radiative opacities are the result of very sophisticated (and, unfortunately, incomplete) theoretical calculations of interaction of atoms and radiation in extremely dense physical environments.…”
Section: Possible Solutionsmentioning
confidence: 99%